Evaluating social programs and problems : visions for the new millennium - Donaldson, Stewart I. (Stewart Ian); Scriven, Michael (Claremont Symposium on Applied Social Psychology Series., 2003)
Today's evaluators are being challenged to help design and evaluate social programs intended to prevent and ameliorate complex social problems in a variety of settings, including schools, communities, and not-for-profit and for-profit organizations. Drawing upon the knowledge and experience of world-renowned evaluators, the goal of this new book is to provide the most up-to-date theorizing about how to practice evaluation in the new millennium. It features specific examples of evaluations of social programs and problems, including the strengths and weaknesses of the most popular and promising.